Analysis of Murabahah Fiqh With A Floating Rate : Overseas Analysis Study - Ramadani, Febriansyah; Mubarok , Jaih; Supriyanto, Trisiladi (CV ODIS, 2023)
There is no doubt that Murabahah contracts are the most frequently discussed and most frequently used in Sharia financial institutions, but it could be said that they also have the most problems. Perhaps one of the most prominent problems faced by Sharia banks is the method of calculating profits in long-term financing contracts. The challenge for Islamic banks is to apply a fixed profit margin with long-term financing of more than 10 years, or this is absolutely impossible because it is impossible for banks to bear the huge risks due to very high inflation resulting in price instability in the market. The research approach uses library research from books and journals combined with field research such as interviews and facts that occur abroad to obtain maximum results. Based on the research results, Murabahah with a floating rate is permitted because Baroatul Asliyah is the permissibility of a law because there is no argument that is prohibited; however, it is limited only to customers who take long-term financing, as for short-term financing under three years, profits are not allowed to change. Qiyasnya, Murabahah financing with a floating rate with changing wages, looking at the benefits side and protecting rights so that no one feels disadvantaged in a sale and purchase agreement, has more positive impacts than negative if applied in Indonesia, seeing and considering the many needs of the community for financing agreements.